The Impact of Faud Star on Detecting Fraudulent Financial Statement - Satria Wibawa; Anjar Sasongko; Haryono Umar (Budapest International Research and Critics University, 2022)
Financial statements are least common but can cause most costly compared to corruption and misappropriation of assets. The purpose of this study was to analyze the effect of Fraud Star elements on Fraudulent Financial Statements (FFS) for the period 2018 to 2020. Each element of the Fraud Star are calculated with financial target proxies (ROA) for pressure, ineffective supervision (BDOUT) for Opportunity, total accruals for Rationalization, Direction Change for capabilities. Lack of Integrity it is calculated by real earnings managemen, and the FFS measurement uses the Beneish M-Score. ACFE, 2020 has released the RTTN which states that the executive level and the accounting department have the 2nd and 3rd highest percentages of fraudsters, respectively 14% and 12%. Banking and financial services are the central public services and are at the heart of economic growth. Therefore the population in this research were banking companies listed on the Indonesia Stock Exchange during the period 2018 - 2020. The research sample was taken using a purposive sampling technique. The data used in this study is secondary data, namely in the form of audited company financial and annual reports and obtained through access to www.idx.co.id and/or the official website of each company. The data analysis method in this study uses panel data regression. The results of the study prove that Opportunity, Rationalization, and Lack of Integrity have a significant positive effect on FFS, while Pressure and Ability, and Internal Audit has not a significant positive effect on FFS